Variability of Marine Carbonate Systems in Seagrass and Coral Reef Ecosystems of Pari and Lombok Islands, Indonesia - Afdal, Afdal; Bengen, Dietriech G.; Wahyudi, A’an Johan; Rastina, Rastina; Purwiyanto, Anna Ida Sunaryo; Prayitno, Hanif Budi; Hamzah, Faisal; Suteja, Yulianto; Adi, Novi Susetyo; Koropitan, Alan F. (Marine Science Department Diponegoro University, 2025)
The increase in anthropogenic CO2 emissions has induced significant physical and biogeochemical alterations in oceans worldwide, including warming, acidification, and oxygen depletion. Coastal areas are particularly vulnerable due to intensified human activities and terrestrial influences, resulting in increased coastal ocean acidification driven by atmospheric CO2 absorption and regional biological and anthropogenic processes. However, research on the collective impact of land-sea interaction and air-sea CO2 exchange on coastal ocean acidification in severely disturbed areas, such as the small islands of Lombok and Pari in Indonesia, remains limited. This study aims to investigate the daily fluctuations in marine carbonate systems and aragonite saturation (Ωarag) levels in the vicinity of seagrass and coral reef habitats in Pari Island and Sire Bay, Lombok. Seawater samples were collected from Sire Bay, Lombok, and the coastal waters of Pari Island to analyze the carbonate systems, CO₂ flux, and metabolic processes. The findings indicate that Pari Island's coastal waters are more susceptible to ocean acidification than Sire Bay, Lombok, showing significantly lower pH values and Ωarag (P<0.05), ranging from 7.60 to 8.00 and 1.04 to 2.54, respectively. This disparity arises from the decreased temperature and salinity in Pari Island's coastal waters during the northwest monsoon, coupled with the deteriorated state of the seagrass and coral reef ecosystems, altering the equilibrium of ecosystem productivity and calcification. The study underscores the necessity of adopting specific coastal management tactics to lessen the effects on fragile ecosystems, highlighting the urgency for additional studies to evaluate adaptive and conservation strategies to preserve coastal biodiversity and ecosystem services.